Characterization and validation of bispecific antibody fragments against transferrin receptor and GABA-A receptor alpha 1 subunit - Koski, Emil (My University, 2023)
Schizophrenia is a mental disorder often characterized by multitude of different symptoms such as psychosis, hallucinations, and cognitive deficiency. While schizophrenia’s pathophysiology is largely unknown, a prevailing hypothesis is that schizophrenia is due to loss of gamma aminobutyric acid (GABA) signaling in frontotemporal brain regions. Current diagnosis relies on behavioral observation; identifying mechanisms of the pathophysiology could provide more accurate diagnosis and treatment. According to this hypothesis reduction in expression of GABA alpha 1 receptors is a major contributor to schizophrenia pathophysiology. To test this hypothesis di-scFv and Fab-scFv bispecific antibody fragments capable of delivering radionuclides necessary for PET were developed. Antibody fragments’ targets were GABAA-receptor’s alpha 1 subunit’s extracellular parts, and transferrin receptor. Transferrin receptor binding would allow the fragments to pass through blood-brain barrier using transcytosis and deliver the antibody fragments into the brain. The aim of this thesis is to produce, characterize and validate these fragments to verify their binding ability to both targets. Preliminary results show that the fragments binded specifically to alpha 1 with similar levels compared to each other. Using fluorescent microscopy Fab-scFv fragments were observed binding to the transferrin receptors and while no direct observation of di-scFv binding to transferrin receptors could be detected, due to some errors made in sample preparation, indirect evidence fom previous studies and Fab-scFv’s transferrin receptor binding would indicate that the di-scFv fragments work as intended as well.
Keywords: bispecific antibodies, schizophrenia, GABA-A receptors